Investigation of the impact of load-induced cracking on the initiation time on steel corrosion in concrete - Persson, Mikael (2000)
This Master dissertation was conducted at the Department of Civil and Mechanical Engineering, University of Dundee, Scotland to obtain a MSc degree from Luleå University of Technology, Sweden. The main objective of this dissertation is to investigate the possibility to obtain a mathematical model to predict the initiation time of steel corrosion in concrete for different crack widths. For this purpose a number of beams were made and cracked to different crack widths in a special rig to simulate load-induced cracks, and then place the specimens into a corrosion tank to accelerate the corrosion process. Due to lack of time to conduct this dissertation the accelerated method used a higher salt concentration (12%) than normal seawater and only one type of concrete (C30) was used with a limited amount of beams for each crack width. To predict the initiation time a half-cell was used with chloride tests to investigate how chlorides propagate through the different cracks. Validerat; 20101217 (root)